On pied-piping : Wh-movement and beyond - Heck, Fabian (Studies in generative grammar ;, 2008)
Pied-piping, the phenomenon that wh-movement may target categories not marked with the feature [wh], has generally been considered idiosyncratic and pathological. On Pied-Piping argues that this assessment is not correct. The book presents a compilation of crosslinguistic generalizations on pied-piping and a theory that derives them. Pied-piping is incorporated into a derivational theory of successive cyclic wh-movement that includes input-output optimization, the operation Agree, and phase theory. The resulting theory is a step towards closing a long-standing gap in syntactic theorizing.